(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Florogenetic analysis showed that the studied flora had started forming since last glacial period with being completely migratory. The two types of relicts – the Valday and Atlantic ones – are established. On the base of synergetic theory the irregularity of specification in time was proved on the different taxonomic levels.